The Effect of Consumer Expectation Index, Economic Condition Index and Crude Oil Price on Indonesian Government Bond Yield - Benny Budiawan Tjandrasa (Universitas Hayam Wuruk Perbanas, 2017)
Governments sell bonds to finance their budget. The investors willing to buy government bonds because of the yield they will get, but on the other hand if government bond yields is Â too high it would burden the state in paying the interest due. Various studies have been done to find the variables that affect government bond yield significantly, such as exchange rate, inflation rate, interest rate, and oil price. This study found two more variables namely consumer expectations index and the economic conditions index to complement the variables that have been discovered. Those two variables are used as a proxy of economic stability of a country, the increase of those variables represent the increase of economic stability and will reduce the level of risk and lowering the yield that investors demand. This research use descriptive method and explanatory study with secondary data using multivariate regression equation model. The results shown consumer expectation index and economic condition index have significant effect on Indonesian Government Bond yield. To keep consumer expectation index and economic condition index increase government should give a positive signal and a sense of security to investor.